The Effect Of Religiousity, Products And Services On Customer Decisions In Using Hajj And Umroh Travel Services In Makassar City - Solihin; Muh Shadri Kahar Muang (JAKA: Jurnal Analisis Kebijakan Kementerian Agama, 2022)
One of the functions of the Hajj and Umrah service institutions is as an intermediary, or as an intermediary so that Hajj and Umrah travel services must be able to attract customers both in terms of products, location services, promotions and much more. Judging by the presence of the Makassar people's concern to use Hajj and Umrah travel services due to the Abu Tour case in Makassar city, there are several factors that might be a benchmark for the Makassar city community to decide to use Makassar Hajj and Umrah travel services, namely religiosity, products and services. . The purpose of this study is to find out how much influence of religiosity, products and services on customer decisions to use services at the Hajj and Umrah travel agencies in Makassar. The research method used is the Quantitative Method. The technique used in determining the sample is Random Sample with the number of samples used amounting to 100 respondents. Data were processed and analyzed using multiple linear regression and using IBM SPSS Statistics 22 for windows. The results showed that the influence of the religiosity variable (X1) had a positive and significant effect of 0.031 < 0.05, the product variable (X2) had a significant positive effect of 0.007 < 0.05 and the service variable (X3) had a significant positive effect of 0.000 < 0, 05. Meanwhile, from the results of the analysis of the coefficient of determination, namely that the influence of religiosity (X1), product (X2), and service (X3) has a significant effect on the decision to use customer service (Y) with a value of 36.1% and the remaining 63.9% is influenced by other variables. , which was not discussed in this study. The most influential variable is the service variable (X3) with a significant value of 0.000 <0.05